Comportamento de progênies meios-irmãos de coentro - de Oliveira, Gustavo Hugo Ferreira [UNESP]; Da Costa, Victor Hugo Barreto; da Silva, Alysson Jalles [UNESP]; De Carvalho Filho, José Luiz Sandes (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2016)
This work evaluated the behavior of coriander half-sib progenies (Coriandrum sativum L.) regarding their agronomic traits. The study was developed in a greenhouse in the Universidade Federal Rural de Pernambuco, PE, Brazil. The experiment was designed as augmented block design with 26 coriander genotypes, of which 24 were coriander half-sib treatments, and two control treatments, ‘Verdão’ and ‘Tabocas’. These progenies were selected from four cycles of phenotypic recurrent selection from the ‘Verdão’ population, which were selected for later bolting. Plant height and canopy diameter were evaluated in the field, and shoot fresh mass. There were significant differences between the treatment means for all variables analyzed. Regarding analysis of variance and SNK test, there is available variability to select half-sib progenies. Genotypes C4-014, C4-015, C4-016, and C4-018 had promising productivity compared to the commercial control varieties. The broad-sense heritability values were 77.3, 81.5 and 95.8% for canopy diameter, shoot fresh mass, and plant height, respectively. This result showed that the majority of phenotypic variance is genetic. Therefore, these genotypes may be used in coriander breeding programs of recurrent selection to obtain cultivars adapted to tropical conditions.
Behavior of half-SIB progenies of coriander
Keywords: Augmented blocks; Coriandrum sativum L.; Recurrent selection